2022
DOI: 10.3390/ijms23063222
|View full text |Cite
|
Sign up to set email alerts
|

HNF1A Mutations and Beta Cell Dysfunction in Diabetes

Abstract: Understanding the genetic factors of diabetes is essential for addressing the global increase in type 2 diabetes. HNF1A mutations cause a monogenic form of diabetes called maturity-onset diabetes of the young (MODY), and HNF1A single-nucleotide polymorphisms are associated with the development of type 2 diabetes. Numerous studies have been conducted, mainly using genetically modified mice, to explore the molecular basis for the development of diabetes caused by HNF1A mutations, and to reveal the roles of HNF1A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 161 publications
(189 reference statements)
1
13
0
1
Order By: Relevance
“…HNF1α is a known transcriptional regulator (Miyachi et al 2022); thus, to investigate the mechanisms underlying islet phenotypes detailed above, we performed RNA sequencing (RNA-seq) to characterize the β cell transcriptome after HNF1A loss (Fig. 3A).…”
Section: Resultsmentioning
confidence: 99%
“…HNF1α is a known transcriptional regulator (Miyachi et al 2022); thus, to investigate the mechanisms underlying islet phenotypes detailed above, we performed RNA sequencing (RNA-seq) to characterize the β cell transcriptome after HNF1A loss (Fig. 3A).…”
Section: Resultsmentioning
confidence: 99%
“…This information may be useful for clarifying the molecular evolution of the hnf1 gene and also functional evolution of the vertebrate liver. Because the inactivation of Hnf1a and Hnf1b in mice results roughly in hepatic functional impairment and biliary abnormality, respectively (El‐Khairi & Vallier, 2016; Miyachi et al, 2022), hnf1 may also regulate hepatic functions in hepatocytes, and biliary epithelial integrity in biliary cells of the hagfish. The question of how hnf1 can work in hepatocytes or biliary cells having different signaling cascades to perform their respective functions is intriguing.…”
Section: Discussionmentioning
confidence: 99%
“…Single genes cause diabetes resulting in a decreased production of insulin hormone in the beta cells [ 1 ]. Global research on the genetics of diabetes has focused on SNPs and gene mutations in nuclear and mitochondrial DNA as well as in different ethnic groups [ 53 ]. Amanda and colleagues’ pilot study on SNPs found that 26 SNPs are linked to T2DM in Hispanic adults [ 54 ].…”
Section: Diabetes In Hispanic and Latino Communitiesmentioning
confidence: 99%